Relief, Recovery, and Revitalization Measures for Tourism and Hospitality Industry During Covid-19 Pandemic: Case Study From Taiwan. (August 2021) - Wu, Li-Fan; Achyldurdyyeva, Jennet; Jou, Wei-Ping; Foung, Wei-Ting; Jaw, Bih-Shiaw
The Covid-19 pandemic has severely disrupted lives and economies around the world. Every part of tourism and hospitality value chain has been affected by the unprecedented travel and mobility restrictions (border control, lockdowns, quarantines, curfews, social distancing) undertaken by governments to contain the spread of the virus. This case study is an in-depth investigation on the Taiwan's government response to support tourism industry stakeholders during Covid-19 pandemic. Data are gathered from a variety of sources, including government policy, procedures, and interviews with business owners and observations of day-to-day business operations. This study presents novel effective government practices and cooperation with tourism and hospitality business during Covid-19 pandemic crisis.